First record of a piebald leucistic smallspotted catshark Scyliorhinus canicula in a special area of conservation, UK - Neil D. Cook; Sarah L. Perry; Declan T. G. Quigley; Jo Cable; Sarah E. Perkins (Marine Biodiversity, 2025)
Colour aberrations are widely reported in vertebrates, but seldom for elasmobranchs. Shark trophic level varies ontogenetically and according to species, so atypical colouration may have implications for ecological fitness both as predator and prey. Here, we present, to our knowledge, the first and only record of a piebald leucistic smallspotted catshark Scyliorhinus canicula from Welsh waters, specifically in the Cardigan Bay Special Area of Conservation, UK. This adds to the five previous observations from the Irish and Mediterranean Seas. Sharks face numerous threats, including the physiological impacts of climate change. In this context, the prevalence and implications of leucism remain a knowledge gap.

Vertebral elemental composition reveals ontogenetic changes in habitat use in a Northeast Atlantic mesopredator shark - Neil D. Cook; Ana Samperiz; Morten Andersen; Edward Inglis; Marc-Alban Millet; Jo Cable; Sarah E. Perkins (Estuarine, Coastal and Shelf Science, 2025)

Insights from the international workshop on “Adapting agriculture to climate change and air pollution” - Evgenios Agathokleous; Lisa Emberson; Jie Pei; Kazuhiko Kobayashi; James D. Blande; Jo Cook; Chao Fang; Zhiyu Han; Hui Ju; Oliver Knopf; Tao Li; Bing Liu; et al. (Environmental Science and Pollution Research, 2024)

Temporal niche partitioning as a potential mechanism for coexistence in two sympatric mesopredator sharks - Neil D. Cook; Abbie Jenkins; Sarah L. Perry; Sarah E. Perkins; Jo Cable (Frontiers in Marine Science, 2024)
Global marine biodiversity declines require bold and ambitious plans to safeguard ecosystem services. Overfishing, habitat loss and projected climate impacts have yielded deleterious effects on marine predators, in particular, driving increasing threat of extinction for many shark species with implications for ecosystem health. Identifying and protecting critical habitat areas for sharks is fundamental to their protection, and may allow for species recovery. Here we use baited remote underwater video stations to investigate spatial and temporal patterns of habitat use by sharks in a Special Area of Conservation (SAC) that is centrally important to the regional blue economy in the UK, the Cardigan Bay SAC. Our results show heterogeneous spatial habitat use and temporal trends in habitat sharing between smallspotted catsharks Scyliorhinus canicula and nursehounds S. stellaris . Nearshore reef habitats are substantially more important than non-reef habitats for both species. The relative abundance of each species, however, is roughly inversely seasonally proportional, with S. canicula and S. stellaris relative abundance highest in March and September, respectively. Temporal niche partitioning may be an important mechanism in marine systems, but has not been widely investigated in sympatric shark communities. These findings are directly relevant for ongoing development of the Welsh Marine Evidence Strategy (2019-2025) and the Welsh National Marine Plan, particularly to inform spatial planning to strengthen the role of SAC management design in protecting important shark areas.

Well-established populations of the western drywood termite, Incisitermes minor (Blattodea: Kalotermitidae), in Korea - Sang-Bin Lee; Sunghyuk Jeong; Hyobin Lee; Yejin Kang; Suseong Lee; Na Ra Jeong; Jaehyeon Lee; Sanghyo Park; Jaewon Kim; Inhyeok Han; Hyeongsu Kim; Jaeyun Kim; et al. (Journal of Asia-Pacific Entomology, 2024)

Assessing the utility of high spectral resolution lidar for measuring particulate backscatter in the ocean and evaluating satellite ocean color retrievals - Brian Collister; Johnathan Hair; Chris Hostetler; Anthony Cook; Amir Ibrahim; Emmanuel Boss; Amy Jo Scarino; Taylor Shingler; Wayne Slade; Michael Twardowski; Michael Behrenfeld; Ivona Cetinić (Remote Sensing of Environment, 2024)

Neurodevelopmental outcomes in children and adults with Fetal Valproate Spectrum Disorder: A contribution from the ConcePTION project - Matthew Bluett-Duncan; Denise Astill; Rana Charbak; Jill Clayton-Smith; Susan Cole; Penny A. Cook; Jo Cozens; Karen Keely; Jacki Morris; Raja Mukherjee; Emma Murphy; Peter Turnpenny; et al. (Neurotoxicology and Teratology, 2023)

Perceptions of a Health Care Notebook from Female Breast Cancer Survivors with Cognitive Impairment - Pamela Moyo; Darrell Walters; Hilary C. Siebens; Jamie Myers; Rachel Baynes; Galen Cook-Wiens; Mi-Yeoung Jo; Arash Asher (Journal of Cancer Education, 2021)

Reported prevalence and quantitative LC-MS methods for the analysis of veterinary drug residues in honey: a review - Ryan Venable; Carion Haynes; Jo Marie Cook (Food Additives & Contaminants: Part A, 2014)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)